Reconfiguring Postwar Class Relations: A Literary Sociology Analysis of The Representation of Laborers and Aristocrats in ‘Lady Chatterley's Lover’ - Nurul Aulia Permana; Nurholis (Jurnal Ilmu Sosial dan Humaniora, 2025)
Lady Chatterley's Lover (2022) is more than just a story of forbidden love; it also depicts the conditions of social class, gender inequality, and one's struggle for independence in a restrictive society. This article, from the point of view of literary sociology, tries to see this film not only as entertainment, but also as a social story that criticizes power relations in marriage, old rules, and noble class levels. The relationship between Lady Constance Chatterley and Oliver Mellors, who come from two vastly different worlds, shows how love can be a way to go against the rules. On the one hand, Connie's marriage to Clifford shows how emotionally alienated she is and the demands of status; meanwhile, her relationship with Mellors grows in a place of freedom-in nature-and reflects her search for a more honest and real relationship. From this analysis, it can be seen that love in this movie is not only about two people falling in love, but also about the struggle to regain control of oneself, choice, and the right to speak-especially for women in a society full of rules. So, Lady Chatterley's Lover is not only about love, but also expresses the desire to be fully human again, in a world that often doesn't care about feelings.